Improving the Students’ Reading Comprehension Using Rare (Review, Answer, Read, Express) At SMPN 2 Palibelo - Firman, Edi (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to see whether the RARE strategy can improve students' reading comprehension at SMPN 2 Palibelo. This research is a class action research (CAR). The data obtained in the form of quantitative and qualitative methods. The instrument used by the researcher was in the form of a test (posttest) in the form of multiple choices. There are four steps to doing: planning, acting, observing, and reflecting. This classroom action research was carried out in two cycles. The first cycle was conducted in two meetings and the second cycle in two meetings. The first cycle was carried out by providing material about the types of vehicles and their existence, in the first cycle there was no increase and it was continued in the second cycle, namely with lots and lots of material, and some several. The results of this study indicate that there is an increase in students' reading in cycle II. Researcher found a significant increase in cycle II, this can be seen from the average cycle of 46 for pre-test, 62.3 for post-test I and 83 for post-test II. So teaching using the RARE strategy shows students are active and enthusiastic in learning English. In addition to the explanation above, the RARE strategy also has several advantages, such as: easy to understand and easy to implement. From the explanation above, the use of the RARE strategy in the learning process of reading comprehension has a positive effect on student achievement, because students can learn easily and relaxed without any burden. I hope this RARE strategy helps more students to improve their reading comprehension.